(untitled) (Nexus International Journal of Science and Education, 2024)
A student-centered classroom is believed to create an environment that promotes student engagement as it focuses on responsibility for their own learning and directly involves themselves in the learning process. This study delved into engagement strategies employed by public elementary school teachers in a student-centered classroom. The study adopted a qualitative approach, utilizing interviews to explore the lived experiences of the teachers as well as their employed engagement strategies to gain valuable insights. The participants were ten (10) public elementary school teachers in Mati, Davao Oriental/The findings shed light on the various experiences encountered by teachers such as the different learning styles of students, culturally diverse classrooms, improved student engagement and motivation, and creating inclusive classrooms. On the other hand, the engagement strategies employed by teachers were differentiated were instruction, reward systems, and active learning strategies. The results also showed valuable insights including the importance of collaborative learning, learning as an active process, and understanding student diversity. The findings of this study revealed the importance of engagement strategies in the implementation of a student-centered classroom. If implemented properly, both students and teachers can create a learning environment that fosters diversity and promotes an active learning experience.